Analisis Kinerja Ekonomi Daerah Hasil Pemekaran (Studi Komparatif Kabupaten Pasaman Barat, Dharmasraya, Solok Selatan) - Rodhiyah, Rodhiyah; Lestari, Weni (Brida Provinsi Jambi, 2023)
Regional Autonomy is implemented so that regions can explore regional potential and be independent in managing existing resources. One of the policies for implementing regional autonomy is the granting of authority to regions to carry out expansion as part of community aspirations. After regional expansion, regions are required to be able to overcome their economic problems, such as increasing economic growth, reducing poverty rates, reducing unemployment rates, improving income distribution, and reducing development inequality. This research aims to see how far the regions resulting from this expansion have developed, An evaluation was carried out by measuring the Economic Performance Index (IKE) in the three districts resulting from the expansion, namely West Pasaman district, Dharmasraya district, and South Solok district. The economic performance index is the result of the average rate of economic growth, the ratio of district GRDP to provincial GRDP, GDP rate per capita, and poverty level. This research uses secondary data with descriptive analysis. The research results show that Dharmasraya district is a district with a better economic performance index than West Pasaman district and South Solok district.